Casa "Mãe". O mesmo Lugar, outro Tempo, outra condição de habitar - Maria João Alves Amaral (2020)
Based on the reinterpretation of a personal reference space as a practical work statement, the present dissertation intends to reflect on how an oversized housing structure allows other interventions and consequent profitability of the interior space. The single-family dwelling under review - the parents' house -, currently inhabited by four people, occupies an implantation area of approximately 441m2, being this discrepancy between its dimensions versus the number of people inhabiting it this dissertation's bottom line. In this perspective, a casa "mãe" - this investigation's object of study - is the name that is attributed to the proposal of the intervention that expresses the intention of rethinking the interior space of the house, by proposing a spatial reorganization and reorientation of its use, via an example of shared occupation, such as cohousing. Therefore, by reinterpreting its design, it not only highlights the importance of family nuclei to remain close, but it also intends to serve as an example and motivate a reflection on the oversized houses in contemporary times